Determinants of Anemia in Adolescent Girls: Literature Review - Pulingmuding, Martha; Hambin, Era Samudra; Imelda, Permadevi; Frety, Endyka Erye (GLOBAL HEALTH SCIENCE GROUP, 2024)
Iron deficiency anemia is anemia that occurs due to a lack of iron in the blood that is prone to occur in adolescent girls. Iron deficiency anemia in adolescents has various consequences, such as impaired physical and mental growth and development and decreased physical fitness, work capacity, and school achievement. The purpose of writing this systematic literature review is to determine the determinants of anemia in adolescent girls. This study was conducted by searching for articles in the Pubmed, BMJ, Coachrane Library, Elvisier databases that have been published with a limitation of 2017 - 2022. The keywords used are determinants, AND anemia AND adolescent girl. Center of Review and Dissemination and The Joana Briggs Institute Guideline as a guide in selecting and determining the quality of the research summarized. The journals selected in writing this systematic literature review are journals that use the Randomized Controlled Trial design. Reporting a systematic literature review uses a checklist from PRISMA. The selection of journals based on the keywords used resulted in 7272 potentially relevant studies totaling 142 duplicates which were then removed until complete articles with titles and abstracts were found in 10 journals. Determinants that influence the incidence of anemia in adolescent girls include education level, family income level, diet, BMI, and activity.